Study of surface layers obtained by copper ion implantation into a target of steel 30Ñ…Ð³ÑÐ½2Ð° by auger Spectroscopy methods - V.V., Ovchinnikov; Yu.M., Borovin; I.A., Kurbatova; E.V., Lukyanenko; N.V., Uchevatkina; S.V., Yakutina (International Journal of Engineering and Technology, 2018)
The relevance of the study due to the necessity of increase in the wear resistance of the tribological parts from steel 30Ð¥Ð“Ð¡Ð2Ð through the copper ions implantation. The leading method for investigating this problem is the examination of the implanted layers of the target surface made of steel 30Ð¥Ð“Ð¡Ð2Ð by means of auger spectroscopy making it possible to review the structure and distribution of the implanted ions comprehensively. The article presents the study results of copper, carbon and oxygen distribution regularities in the surface layers formed during copper implantation into the plates from steel 30Ð¥Ð“Ð¡Ð2Ð in the impulsive ions source. It has been established that in the process of copper implantation, a carbon layer with a thickness of ~ 50 nm is formed on the surface. It is shown that in the intermediate layer (up to 100 nm), the iron is partly in the oxidized condition. The possible mechanisms of the influence of surface layers structure formed in the result of copper implantation into the steel plate 30Ð¥Ð“Ð¡Ð2Ð on their tribological characteristics are presented. The article materials are of practical value in developing the technology for wear resistance increase of the various parts of the revolution shape used in aircraft movable joints.Â Â
Keywords: Implantation; Auger Spectroscopy; Tribological Properties; Surface Layers; Carbon Steel; Wear; Copper Content.